2022
DOI: 10.3389/fsurg.2022.886438
|View full text |Cite
|
Sign up to set email alerts
|

Management of Posterior Fossa Tumors in Adults Based on the Predictors of Postoperative Hydrocephalus

Abstract: ObjectiveThis study aims to identify the predictors of postoperative hydrocephalus in patients with posterior fossa tumors (PFTs) and guide the management of perioperative hydrocephalus.MethodsWe performed a single-institution, retrospective analysis of patients who underwent resection of PFTs in our department over a 10-year period (2011–2021). A total of 682 adult patients met the inclusion criteria and were divided into either a prophylactic external ventricular drainage (EVD) group or a nonprophylactic-EVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…There are several possible reasons to explain the role of lesion size. Corroborated with the previous works, the inherent characteristics of the surgery, longer operative times, more perioperative bleeding, more irritation of the ventricular surfaces, or more spillage of neoplasms cells or a combination of these factors, could have contributed to the condition [4,6,9,21,[23][24][25][26]. Second, causation can be speculated to growth kinetics.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There are several possible reasons to explain the role of lesion size. Corroborated with the previous works, the inherent characteristics of the surgery, longer operative times, more perioperative bleeding, more irritation of the ventricular surfaces, or more spillage of neoplasms cells or a combination of these factors, could have contributed to the condition [4,6,9,21,[23][24][25][26]. Second, causation can be speculated to growth kinetics.…”
Section: Discussionmentioning
confidence: 80%
“…The ventricular in ltration could represent a signi cant indicator for hydrocephalus risk strati cation of patients with medulloblastoma at the point of postresection. Three previous studies have investigated the association between ventricular in ltration and necessitating permanent shunt [23,25,26]. The chronic or late-onset symptomatic persistent hydrocephalus after resection could be driven by a direct effect of medulloblastoma and might be explained by several hypotheses, including obstructive and noncommunicating.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with the findings from studies that have explored the outcomes of adult PF resection with the operating microscope. Zhang et al 23 observed the management of 675 adult patients with PF tumors where surgeons were able to achieve GTR in 96.7% of patients. In addition, they reported a 3.6% and 3.9% incidence of postoperative hydrocephalus and hemorrhage, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Kendall tau correlation coefficient between GOS and KPI. KPI = Karnofsky Performance Index; GOS = Glasgow Outcome Score a rate of hydrocephalus after posterior fossa surgery to be 2% to 7% in adult patients 13 .…”
Section: Discussionmentioning
confidence: 99%